2013
DOI: 10.1111/flan.12036
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook Data to Analyze Learner Interaction During Study Abroad

Abstract: Although study abroad is viewed as an ideal environment for interaction in the target language, research in this area has relied mostly upon self‐reported data, which pose challenges regarding recall bias and participant commitment. This article shows how Facebook data can be used to analyze naturally occurring learner interactions during study abroad. Drawing from a 10‐month, Web‐based ethnography of three learners, findings indicate an overall increase in Portuguese use during study abroad, as well as acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
(47 reference statements)
2
28
0
1
Order By: Relevance
“…The recording took place without prior notice of the subjects. It was purposively implemented to avoid Hawthorne Effect where the participants behave unnaturally realizing that they are being research (Back, 2013:Haghverdi, 2010. However, when the data collection finished, the subjects were told about the recording.…”
Section: Methodsmentioning
confidence: 99%
“…The recording took place without prior notice of the subjects. It was purposively implemented to avoid Hawthorne Effect where the participants behave unnaturally realizing that they are being research (Back, 2013:Haghverdi, 2010. However, when the data collection finished, the subjects were told about the recording.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative SA studies have analyzed these same types of variables as constructions, such as the social construction of gender in connection to themes found in the data (e.g., Allen, ; Du, ; Goldoni, ; Polanyi, ). Studies employing mixed methods have used qualitative data to elucidate quantitative patterns, and vice versa (e.g., Back, ; DeKeyser, ).…”
Section: Internal and External Variables: Toward A Multidimensional Amentioning
confidence: 99%
“…In addition, L2 writing and L2 listening comprehension continue to be underresearched, with a few exceptions (e.g., Cubillos et al [2008] for L2 listening; Godfrey, Treacy, & Tarone [2014] for L2 writing). Future research can take advantage of the increasing use of digital platforms in SA contexts (e.g., e-mail, e-journals, blogs, and social media) and make use of these sources of data for L2 writing studies (e.g., Back, 2013;Stewart, 2010). Finally, even though scholars are progressively examining the linguistic and nonlinguistic effects of short-term SA programs (e.g., Allen, 2010;Arnett, 2013;Castañeda & Zirger, 2011;Cubillos et al, 2008;Martinsen, 2010;Shiri, 2015), new research looking at the benefits of short-term SA programs needs to equally investigate all areas of L2 ability, including those that seem to be less likely to change in immersive contexts such as L2 grammar.…”
Section: And Accuracymentioning
confidence: 99%
“…In their studies, Aspey (2011) and Castro (2012) found that students join instruction activities easier with online lessons than traditional lessons and educators like to use social media in their teaching process. Back (2013) stated that some social media tools such as Facebook are playing an important role for language learners. Similarly, Meishar-Tal, Kurtz, and Pieterse (2012) used Facebook as a learning management system (LMS) in their study.…”
Section: Introductionmentioning
confidence: 99%